Mesto mikofenolata v nefrologiji - Bren, Andrej (Medicinski razgledi, 2006)
The contribution focuses on one of the more recent immunosuppressive drugs, mycophenolate, which is available as mycophenolate mofetil and sodium mycophenolate. The active substance of both compounds is mycophenolic acid. The pharmacodynamics and pharmacokinetics of the active substance are presented. The broadest application of mycophenolate in nephrology is in kidney transplantation, which has resulted in less rejections of kidney graftsand better survival of grafts and patients. Limited success have been obtained in the treatment of some forms of lupus nephritis, systemic vasculitis, membranous nephropathy, focal and segmental glomerulosclerosis andglomerulonephritis with minimal changes, IgA nephropathy and acute interstitial nephritis.
Keywords: Kidney Transplantation; Ledvica, bolezni; Ledvica, presaditev; Kidney Diseases; Lupusni nefritis; Mycophenolic Acid; Lupus Nephritis; Mikofenolna kislina; Vasculitis; Vaskulitis; Glomerulonefritis; Glomerulonephritis; Immunosuppressive Agents; Imunosupresivi; farmakologija; drug; zdravila; nefrologija; mikofenolat; farmakodinamika